Perlindungan Hukum Hak Pekerja Usaha Mikro Kedai Kopi - Kamila, Uswatun; Suhermi, Suhermi (Zaaken: Journal of Civil and Business Law, 2023)
This study aims to analyze the implementation of legal protection for the rights of workers in the Coffee Shop Micro Enterprise in Telanaipura District, Jambi City, and to determine the obstacles in the implementation of workers’ rights and their resolution. The type of research used in this paper is Juridical Empirical research and the sampling was taken based on purposive sampling. From the results of this study it can be seen that: (1) legal protection for coffee shop micro business workers based on applicable labor regulations has not been properly fulfilled because there is still non-compliance by employers in complying with labor regulations, (2) as well as a lack of legal knowledge and awareness both from employers and workers who become obstacles are not properly implemented to fulfill the rights that should be obtained by workers in an employment relationship. Of course these existing problems cannot escape the government’s lack of attention to labour, the government should conduct a review of workers whether they have fully obtained their rights or not. Abstrak Penelitian ini bertujuan untuk menganalisis pelaksanaan perlindungan hukum terhadap hak pekerja Usaha Mikro Kedai Kopi di Kecamatan Telanaipura Kota Jambi, dan untuk mengetahui kendala dalam pelaksanaan hak pekerja serta penyelesaiannya. Tipe penelitian yang digunakan dalam penulisan ini ialah penelitian Yuridis Empiris dan penarikan sampel diambil berdasarkan purposive-sampling. Dari hasil penelitian ini dapat dilihat bahwa: (1) perlindungan hukum terhadap pekerja usaha mikro kedai kopi berdasarkan peraturan ketenagakerjaan yang berlaku belum terpenuhi dengan baik karena masih ada ketidakpatuhan pengusaha dalam mentaati peraturan mengenai ketenagakerjaan, (2) serta kurangnya pengetahuan dan kesadaran hukum baik dari pengusaha maupun pekerja yang menjadi kendala tidak terlaksana dengan baik pemenuhan hak yang seharusnya didapatkan oleh pekerja dalam suatu hubungan kerja. Tentu permasalahan yang ada tersebut tidak luput dari kurangnya perhatian pemerintah terhadap tenaga kerja, seharusnya pemerintah melakukan peninjauan terhadap pekerja apakah telah mendapatkan hak mereka sepenuhnya atau tidak Â